ANALISIS BEBAN KERJA DAN KELELELAHAN KERJA KARYAWAN FRONT LINER DI INSITITUSI âXâ - Zuraida, Rida; Jorinatan, Andi; Perkasa, Henrico; Senjaya, Richard (Industrial and Systems Engineering Assessment Journal (INASEA), 2013)
Fatigue is generally experienced in working as a result of employee workload. Employees at theÂ Institution X have unique perceived workload. Their workload can lead to the onset of excessive fatigue, andÂ leading to decrease in productivity. This study aims to determine the fatigue of employee subjectively throughÂ questionnaires that measure perceptions of fatigue felt by employees using KAUPK2, as well as the potential for fatigue using Fatigue likelihood scoring (FLS), and individual fatigue likelihood scoring (IFLS). The result ofÂ fatigue questionnaire (KAUPK2) among all 17 employees has a good value of alpha cronbach 0.8 which showedÂ fatigue at safe levels.It indicated that men and women feel the same feelings of fatigue associated (t value = 1.75Â < 2.37). It means workload given by the Institute can be tolerated by the physical and psychic abilities ofÂ employees. While the value of FLS, and IFLS in line with the results of the questionnaire â a a relatively safeÂ level is at level 2 and level 3 for the FLS and 0 and 1 for IFLS correlation test between the two â showed noÂ significant relationship. For dealing with risks that may occur due to employee fatigue in the future, institutionÂ may make an effort so that the employee would be more responsible for the self-recovery process. The institutionÂ could also set the working time to make sure that employee would have enough time for resting, and wouldÂ identify the likelihood of excessive fatigue periodically.